Experiences of Intimate Partner Violence Victims With Police and the Justice System in Canada - Saxton, Michael D. (Journal of interpersonal violence, 2021)
Legal responses to intimate partner violence (IPV) can determine whether and how those exposed to IPV seek help. Understanding the victim’s perspective is essential to developing policy and practice standards, as well as informing professionals working in policing and the justice system. In this survey study, we utilized a subset of 2,831 people who reported experiencing IPV to examine (a) rates of reporting to the police; (b) experiences with, and perceived helpfulness of, police; (c) rates of involvement with the criminal and family law systems, including protection orders; and (d) experiences with, and perceived helpfulness of, the justice system. Data were analyzed using descriptive statistics for closed-ended survey questions and content analysis of text responses. More than 35% of victims reported a violent incident to the police, and perceptions of helpfulness were mixed. Fewer victims were involved with the criminal and family law systems, and their satisfaction also varied. Text responses provided insight into possible reasons for the variability found in experiences, for example, the proposed role of victim and system expectations, and respondents’ perception that getting help depends on “being lucky” with the officials encountered.